Equal partnership between unequal regions? Assessing deliberative parliamentary debate in ACP-EU relations. Issue 4 (3rd July 2016) - Delputte, Sarah; Williams, Yentyl
Abstract: This paper develops an analytical framework to assess the quality of deliberation in the ACP-EU Joint Parliamentary Assembly (JPA). Despite rhetoric on 'equal partnership' between ACP and EU countries, academic assessments of the Cotonou Agreement point to the lasting asymmetrical power relationship, most visible in the Economic Partnership Agreements (EPAs) negotiations. However, this paper assesses to what extent the JPA debate on EPAs can approach the ideal type of deliberation. The empirical investigation is based on participatory observation, semi-structured interviews and an analysis of primary documents, including the attendance lists of 29 JPA sessions, more than 40 resolutions and 120 parliamentary questions related to the trade-development nexus.